2013
DOI: 10.5888/pcd10.130029
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Physical Activity and Nutrition Intervention: Barriers, Enablers, and Preferred Strategies for Workplace Obesity Prevention, Perth, Western Australia, 2012

Abstract: IntroductionWorkplace health promotion programs to prevent overweight and obesity in office-based employees should be evidence-based and comprehensive and should consider behavioral, social, organizational, and environmental factors. The objective of this study was to identify barriers to and enablers of physical activity and nutrition as well as intervention strategies for health promotion in office-based workplaces in the Perth, Western Australia, metropolitan area in 2012.MethodsWe conducted an online surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 19 publications
7
38
0
2
Order By: Relevance
“…In particular, Blackford et al (2013) reported that the most commonly reported barriers were related to work, which is consistent with the results of the present study. In the present study, 70.4% of the sufficiently active group and 59.3% of the insufficiently active group reported work-related barriers, which was the most frequently reported category of barriers by both physical activity groups.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In particular, Blackford et al (2013) reported that the most commonly reported barriers were related to work, which is consistent with the results of the present study. In the present study, 70.4% of the sufficiently active group and 59.3% of the insufficiently active group reported work-related barriers, which was the most frequently reported category of barriers by both physical activity groups.…”
Section: Discussionsupporting
confidence: 82%
“…Barriers identified in this study and previously reported in literature examining the general population of adult men included (1) lack of time, (2) lack of motivation, (3) lack of financial resources, (4) lack of an exercise partner, (5) busy/too many commitments at work, and (6) work late/long hours (e.g., Blackford et al, 2013;Brownson et al, 2001;Plotnikoff et al, 2004;Sequeira et al, 2011). In particular, Blackford et al (2013) reported that the most commonly reported barriers were related to work, which is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Taking into account the large part of the day that most adults spend in their workplace, worksites offer unique opportunities to encourage employees and their families to engage in regular physical activity [12]. Interventions aiming at improving physical activity of employees should be evidence-based and should consider socio-economic, lifestyle, organisational and environmental factors [13]. No previous studies had assessed the pattern and correlates of domain-specific physical activity among middle-aged employees.…”
Section: Sample Designmentioning
confidence: 99%